Tecnologia BIM em obras: orçamento e planejamento - Bruna de Abreu Murta (2023)
The BIM (Building Information Modeling) methodology is currently the best way to reduce failures, decrease costs, optimize processes, and even plan construction projects more securely. Thus, this work aims to identify how BIM technology can be utilized for the preparation of budgets and planning of private and public works, taking into account the possible difficulties arising from the bidding processes currently used. It is believed that the use of this technology can reduce inconsistencies in budget spreadsheets, which are of even greater importance in bidding processes, as the prices proposed cannot be altered once submitted. However, the traditional public administration contracting model in Brazil, which separates projects, budgeting, and execution, hinders the full utilization of this methodology, which primarily aims to integrate all parties involved in the process. To this end, exploratory research was conducted presenting theoretical references on budgeting and project planning, on norms and laws related to public works, and on BIM technology. Subsequently, four case studies conducted by other authors on the subject of this research were analyzed. This analysis showed that the use of BIM accelerates the process of quantification, reduces human errors, and allows for quick simulations of different possibilities. However, there is a need for greater dissemination of this technology and qualification of professionals for BIM utilization.